The Effectiveness of Group Cohesiveness Training in Reducing Social Loafing - Rosalia Katarina Lamanepa; M. K. P. Abdi Keraf; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2021)
Abstract: Group cohesiveness training is a series of processes to develop and improve work by attracting group members and being motivated to remain within the group. This study aims to determine whether group cohesiveness training is effective in reducing social loafing on a group of women’s empowerment family head (PEKKA). This study used an experimental method with a one-group pretest-posttest research design. The subjects of this study used a total population of 28 subjects and only 25 people attended the training until completion. Using 4 aspects namely self-esteem, problem-solving, task cohesiveness, and social cohesiveness. Measure training using Mulvey's Social Loafing Scale and Carron's Cohesion Scale. Data analysis using paired sample test. Based on the analysis of research data, social loafing variables scored 0.337, and group cohesiveness scored 0,000. This shows that group cohesiveness training is less effective in reducing social loafing but is effective in increasing group cohesiveness. Abstrak: Pelatihan kohesivitas kelompok adalah serangkaian proses untuk mengembangkan serta meningkatkan kerja dengan menjadikan anggota kelompok saling tertarik dan termotivasi untuk tetap berada dalam kelompok tersebut. Penelitian ini bertujuan untuk mengetahui apakah pelatihan kohesvitas kelompok efektif untuk menurunkan social loafing pada kelompok Pemberdayaan Perempuan Kepala Keluarga (PEKKA). Penelitian ini menggunakan metode eksperimen dengan desain penelitian one-group pretest posttest. Subjek penelitian ini menggunakan keseluruhan jumlah populasi sebanyak 28 subjek dan hanya 25 orang yang mengikuti pelatihan hingga selesai. Menggunakan 4 aspek yakni harga diri, problem solving, kohesivitas tugas dan kohesivitas sosial. Pengukuran pelatihan menggunakan skala social loafing dari Mulvey dan skala kohesvitas dari Carron. Analisis data menggunakan paired sample test. Berdasarkan analisis data penelitian, variabel social loafing mendapat nilai 0,337 dan kohesivitas kelompok mendapat nilai 0,000. Ini menunjukkan bahwa pelatihan kohesvitas kelompok kurang efektif menurunkan social loafing tetapi efektif menaikkan kohesvitas kelompok.